Reactive Distillation of Glycolic Acid Using Heterogeneous Catalysts: Experimental Studies and Process Simulation - Mutschler, Carole; Aparicio, Juliana; Mokbel, Ilham; Capron, Mickaël; Fongarland, Pascal; Araque, Marcia; Nikitine, Clémence (Frontiers in Chemistry, 2022)
The glycerol oxidation reaction was developed leading to selective catalysts and optimum conditions for the production of carboxylic acids such as glycolic acid. However, carboxylic acids are produced in highly diluted mixtures, challenging the recovery and purification, and resulting in high production costs, polymerization, and thermal degradation of some of the products. The protection of the acid function by esterification reaction is one of the most promising alternatives through reactive distillation (RD); this technique allows simultaneously the recovery of carboxylic acids and the elimination of most part of the water. The reactive distillation, experimental and simulation, of glycolic acid was performed, based on kinetic and thermodynamic models developed. For the thermodynamic model, binary parameters of the missing couples were determined experimentally, and the non-random two-liquid (NRTL) model was selected as the most suitable to represent the binary behavior. The kinetic study of the esterification in the presence of homogeneous and heterogeneous catalysis concluded that the heterogeneous reaction can be accurately described either by a pseudo-homogeneous model or the Langmuir–Hinshelwood (L-H) adsorption model. Reactive distillation was conducted in a distillation column filled with random packing sulfonated ion-exchange resin, Nafion NR50®, or with extruded TiO2-Wox. The conversion rate of glycolic acid in reactive distillation increases from 14% without catalyst to 30% and 36% using Nafion NR50® and TiO2-Wox, respectively. As opposed to the batch reactor study, the conversion rate of glycolic acid was better with TiO2-Wox than with sulfonated ion-exchange resin. The better performance was related to an increase in the hydrodynamics inside the column. Tests using water in the feed confirm the hypothesis by increasing the conversion rate because of the decrease in the mass transfer resistance by reducing the average diffusion coefficient. The simulation of the reactive distillation column with ProSim® Plus showed that the yield of the ester increased operating at a low feed rate with reactive stripping. In the presence of water in the feed, nonreactive stages are required, including an enrichment region to separate water vapor.